CpG island hypermethylation-associated silencing of microRNAs promotes human endometrial cancer - Li, Bi-Lan (BioMed Central, 2013)
BACKGROUND: Endometrial cancer (EC) is the most common gynecologic malignancy, but the molecular events involved in the development and progression of EC remain unclear. This study aimed to explore epigenetic modification of genes and miRNAs involved in EC development. METHODS: Ishikawa and AN3CA cells were treated with 5’-Aza-2-deoxycytidine or histone deacetylase inhibitor. The expression of miRNAs and related genes were detected by PCR and Western blot. Promoter methylation was detected by bisulfite specific PCR sequencing. The proliferation, colony formation, cell cycle progression, migration and invasion of EC cells were evaluated by MTT, soft agar assay, flow cytometry, wound healing and invasion assay, respectively. RESULTS: Aberrant expression of miRNAs including miR-200b, miR-130a/b, miR-625 and miR-222 was associated with tumorigenesis and metastasis in endometrial cancer. Silencing of miR-130b induced E-cadherin expression, while ectopic expression of miR-130b and knockdown of DICER1 increased the expression of Vimentin, zeb2, N-cadherin, Twist and Snail in EC cells. Furthermore, 5’-Aza-2-deoxycytidine and Histone deacetylase (HDAC) inhibitor inhibited the proliferation, colony formation, migration and invasion of EC cells, accompanied by reduced MMP secretion. CONCLUSIONS: Our study provides the first description of epigenetic modification of epithelial mesenchymal transition associated genes and miRNAs in EC cells, which are extensively involved in the regulation of gene expression and subsequent accumulation of malignant features of EC cells.